Diseño de una máquina trituradora para plástico pet (2020)
Initially, an information search was carried out on the crushing process of the PET plastic bottles, through which an overview of the problem that originated around this material could be obtained, then a collection of small and small data was carried out. medium recycling companies to determine the parameters and requirements to which the machine would work. Then an information search was carried out which allowed to determine the current technologies used in the crushing of PET, knowing the above a series of alternatives were executed that allowed to select one of the subsystems of the machine and that in turn met the established parameters initially.